PENGEMBANGAN KEMAMPUAN REPRESENTASI MATEMATIS SISWA MELALUI STRATEGI REACT DALAM MATERI PECAHAN DI SMP - Martina, Dina; ., Sugiatno; ., Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This study aims to analyze the ability of students' mathematical representation in solving the problem of fractions after being taught by REACT strategy. This research is a research action (action reseacrh) to 9 students in class VII SMP Negeri 1 Sanggau West Kalimantan Province. Data collection used pretest and posttest methods of mathematical representation and interview after treatment. The results of data analysis show that the ability of mathematical representation to be better, with increasing the potential of students' intelligence in using representational model. It can be concluded that the students were able to solve the fractional sum problem involving representational models in verbal form and presented back into the symbolic form representation model.  Keyword: Mathematical Representation, REACT Strategy.